Height transformation between SVS2000/Trst and SVS2010/Koper with the national height transformation model* - Koler, Božo (Geodetski vestnik, 2025)
In this paper we present the creation of a national height transformation model that allows the transformation of heights between the old (SVS2000/Trieste) and the new height system (SVS2010/Koper) and vice versa. The height transformation surface - SLO-VTP2024 was created on the basis of 2,116 height differences between the old and the new height system on benchmarks evenly distributed across Slovenia. The height transformation surface - SLO-VTP2024 and SLO-VTP2024 accuracy surface is determined by the kriging interpolation method with additional influence of the variogram and written in the form of a cell grid. The ViTra software package is presented, which enables the height transformation on the basis of optimized bilinear interpolation equations. The quality of SLO-VTP2024 was assessed on the basis of the differences between the calculated heights and the heights determined by the transformation at the points for determining the height transformation surface – 2,116 benchmarks, at 8,775 and 8,695 control benchmarks, on control benchmarks belonging to different orders of the levelling network, on control benchmarks stabilized in individual loops of the new 1st order Slovenian levelling network, and by area and benchmarks stabilized in individual city levelling networks.
Keywords: accuracy of height transformation surface; analiza kakovosti; celična mreža; cell grid; geodesy; geodezija; height transformation model; height transformation surfaces; ploskev natančnosti višinske transformacijske ploskve; programski paket ViTra; quality analysis; višinska transformacijska ploskev; višinski transformacijski model; ViTra software package